Agent-Mediated Electronic Commerce. Designing Trading Strategies and Mechanisms for Electronic Markets AMEC 2010, Toronto, ON, Canada, May 10, 2010, and TADA 2010, Cambridge, MA, USA, June 7, 2010 Revised Selected Papers - David, Esther; Larson, Kate.; Rogers, Alex.; Shehory, Onn.; Stein, Sebastian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This volume contains 9 thoroughly refereed and revised papers detailing recent advances in research on designing trading agents and mechanisms for agent-mediated e-commerce. They were originally presented at the 12th International Workshop on Agent-Mediated Electronic Commerce (AMEC 2010), collocated with AAMAS 2010 in Toronto, Canada, or the 2010 Workshop on Trading Agent Design and Analysis (TADA 2010), collocated with EC 2010 in Cambridge, MA, USA. The papers examine emerging topics such as ad auctions and supply chains, or the interactions between competing markets, and present novel algorithms and rigorous theoretical results. Several of them evaluate their results using real data from large e-commerce sites or from experiments with human traders.
Rank and Impression Estimation in a Stylized Model of Ad Auctions -- Network Effects in Double Auction Markets with Automated Traders -- Modeling Seller Listing Strategies -- A Grey-Box Approach to Automated Mechanism Design -- Flexibly Priced Options: A New Mechanism for Sequential Auctions with Complementary Goods -- Search Costs as a Means for Improving Market Performance -- Setting Fees in Competing Double Auction Marketplaces: An Equilibrium Analysis -- Human Traders across Multiple Markets: Attracting Intra-marginal Traders under Economic Experiments -- Time Constraints in Mixed Multi-unit Combinatorial Auctions.
Keywords: Computer science; Information technology; Business -- Data processing; Artificial intelligence; Application software; E-commerce.; Computer Science; e-Commerce/e-business.; IT in Business; Artificial Intelligence (incl. Robotics).; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl. Internet).; Electronic books